2017
DOI: 10.1177/0267659117733810
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive blood conservation program in a new congenital cardiac surgical program allows bloodless surgery for the Jehovah Witness and a reduction for all patients

Abstract: The continuous application and development of blood conservation techniques across the continuum of care allowed bloodless surgery for JW and non-JW patients alike. Blood conservation is a team sport and to make significant strides requires participation and input by all care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…The study noted that there were no clinically significant differences in outcomes measured between the two cohorts, demonstrating the positive impact of EPO for patients refusing transfusion and hence supports its use for Witness patients. 8 Eleven comparative studies discussing outcomes between Witnesses and non-Witnesses were found 2,16,21,[45][46][47][48][49][50][51][52] (Table 2) and these often gave agents to increase the preoperative Hb. This varied between studies and makes comparison more challenging.…”
Section: Pre-operativementioning
confidence: 99%
See 2 more Smart Citations
“…The study noted that there were no clinically significant differences in outcomes measured between the two cohorts, demonstrating the positive impact of EPO for patients refusing transfusion and hence supports its use for Witness patients. 8 Eleven comparative studies discussing outcomes between Witnesses and non-Witnesses were found 2,16,21,[45][46][47][48][49][50][51][52] (Table 2) and these often gave agents to increase the preoperative Hb. This varied between studies and makes comparison more challenging.…”
Section: Pre-operativementioning
confidence: 99%
“…2,45,[48][49][50][51][52] Six of the 11 comparative studies in Table 2 which reported the outcome of blood loss did so differently, making direct comparison difficult. 2,21,48,[50][51][52] However, within the studies themselves, two found that the Witness group experienced significantly less postoperative blood loss compared to the non-Witness control (Witness vs non-Witness: 466.8 vs 843 mL, p = 0.0001; 45 312 ± 141 vs 721 ± 619 mL, p < 0.05 50 ). This may be explained by more careful surgery and the blood conserving strategies discussed in the studies.…”
Section: Post-operativementioning
confidence: 99%
See 1 more Smart Citation
“…Collected scientific literature [1][2][3] and patients' ideals, we discussed with Anesthesiologists of our Cardiac Anesthesia Department and hence we wrote a protocol to treat the patients that refuse blood products transfusions in the most of cardiac surgery procedures except in some complex operative technique as heart transplantation or aortic arch surgery or debranching surgery in deep hypothermia. We drafted the protocol, that was approved by the hospital and warmly accepted and appreciated by the Jehovah's health exponents, and we started to treat the patients who refused blood products transfusion respecting their wills.…”
Section: Editorialmentioning
confidence: 99%
“…There is a single meta-analysis of 6 studies comparing outcomes of 564 JWs with 903 matched controls 5 with the majority of reports of cardiac surgery in JW patients refusing blood transfusions being single-centre studies with relatively small patient numbers. [6][7][8][9][10][11][12] In part, this is a reflection of the very small proportion of JWs in the population (USA: 0.6%, Canada and Australia/New Zealand: 0.3%, Britain: 0.2%). 13 These studies reveal no accurate detail of the modifiable factors of the conduct of cardiopulmonary bypass (CPB), including blood flow and pressure, nadir haemoglobin (Hb), oxygen delivery (DO 2 ) and blood conservation measures, that are known to influence patient outcome.…”
Section: Introductionmentioning
confidence: 99%